Regiospecific Photochemical Synthesis of Methylchrysenes - Thomas Böhme; Mari Egeland; Marianne Lorentzen; Mohamed F. Mady; Michelle F. Solbakk; Krister S. Sæbø; Kåre B. Jørgensen (Molecules, 2022)
Methylated polycyclic aromatic hydrocarbons (PAHs) are suspected to be some of the toxic compounds in crude oil towards marine life and are needed as single compounds for environmental studies. 1-, 3- and 6-methylchrysene (3a,b,c) were prepared as single isomers by photochemical cyclization of the corresponding stilbenoids in the Mallory reaction using stoichiometric amounts of iodine in 82-88% yield. 2-methylchrysene (3d) was prepared by photochemical cyclization where the regioselectivity was controlled by elimination of an ortho-methoxy group under acidic oxygen free conditions in 72% yield. These conditions failed to form 4-methylchrysene from the corresponding stilbenoid. All stilbenoids were made from a common naphthyl Wittig salt and suitably substituted benzaldehydes. We have also demonstrated that methylchrysenes can be oxidized to the corresponding chrysenecarboxylic acids by KMnO4 in modest yields.